Optimal Costal Cartilage Graft Selection According to Cartilage Shape: Anatomical Considerations for Rhinoplasty - Bender-Heine, Adam N.; Zdilla, Matthew J.; Russell, Michelle L.; Rickards, Allen A.; Holmes, J. Scott; Armeni, Mark A.; Lambert, H. Wayne (Facial Plastic Surgery, 2017)
Costal cartilage grafting is a commonly used reconstruction procedure, particularly in rhinoplasty. Although costal cartilage is broadly used in reconstructive surgery, there are differing opinions regarding which costal cartilage levels provide the most ideal grafts. Grafts are typically designed to match the shape of the recipient site. The shapes of costal cartilage grafts have been described as “boat-shaped,” “C-shaped,” “canoe-shaped,” “U-shaped,” “crescent-shaped,” “L-shaped,” “semilunar,” “straight,” and “Y-shaped.” The shapes of costal cartilages are thought to lend themselves to the shapes of certain grafts; however, there has been little study of the shapes of costal cartilages, and most reports have been anecdotal. Therefore, this study is aimed to detail the average shapes of the most commonly grafted cartilages (i.e., the fifth to seventh cartilages). A total of 96 cadaveric costal cartilages were analyzed through geometric morphometric analysis. The fifth costal cartilage was determined to have the straightest shape and would therefore be particularly suitable for nasal dorsum onlay grafting. The lateral portions of the sixth and, particularly, the seventh costal cartilages have the most acute curvature. Therefore, they would lend themselves to the construction of an en bloc “L”-shaped or hockey stick-shaped nasal dorsum-columellar strut graft.
Keywords: rhinoplasty; cartilage grafting; cartilage harvest; facial reconstruction; nasal reconstruction